In vitro modulatory effects of quercetin on bovine neutrophil effector functions - Chuammitri P. (Chulalongkorn University, 2015)
Bovine neutrophils perform numerous effector functions to overcome microbial invasions by utilizing innately-equipped intracellular and extracellular killing mechanisms. In this study, we explored the modulatory effects of quercetin hydrate (QH), an herbal flavonoid compound, on bovine neutrophil functional activities. Isolated neutrophils were incubated with various concentrations of QH (0-100 μM). Neutrophil viability results showed no signs of cytotoxicity (p = 0.33). In other assays, neutrophils were stimulated with a pre-defined concentration of QH (50 μM). Results showed promising effects of QH on enhancing intracellular ROS generation (p < 0.0001) compared to control. Phagocytic activity of fluorescently labeled E.coli was also augmented by the effects of this compound (p = 0.05). However, intracellular killing of live E.coli quantified by MTT assay demonstrated a slight decrease in activity (p = 0.304). Additionally, extracellular killing driven by NET-DNA release was remarkably higher in QH-stimulated cells (p = 0.0004). Supplementation of QH to LPS stimulated neutrophils resulted in significantly decreased pro-inflammatory cytokines, IL-1β (p < 0.0001) and TNF-α gene expression (p = 0.004). Taken together, quercetin could exert its noteworthy actions, both at cellular and molecular levels, at a certain physiological concentration.